Satisfaction survey of basketball fans at the example of the club Twarde Pierniki - Andżelika Dzięgiel (Kazimierz Wielki University, 2016)
Increasing the quality of service is one of a main objective of service companies, including sporting organizations. A significant increase of leisure activities has influence on strong competition among the organizers of the cultural, social and sport events. The regular surveys of satisfaction are one of the elements of relationship marketing, which are necessary to get the high attendance of fans on events, e.g. basketball matches. In the article as an object of study has been chosen the club Twarde Pierniki. The main objective of the research was the assessment satisfaction from sports products offered by the basketball club and improvement their quality based on responses received from the customers - basketball fans. In 2015 by means of on-line survey method was conducted research in which participated 235 respondents. The results showed that the evaluations of organization of sports event (basketball matches, additional attractions), marketing and social activities of the club, as well merchandise in The Fan Shop, are high. Only The Fan Club was rated lower than other components of the club activities.